High capacity and fast Na+ transport in the SbPS4 material by Bi3+ substitution for sodium-ion batteries. Issue 24 (7th November 2022) - Yin, Qi-Min; Gu, Zhen-Yi; Lü, Hong-Yan; Guo, Weiping; Du, Miao; Liu, Yi-Tong; Liu, Yan; Heng, Yong-Li; Luo, Zhong-Zhen; Wu, Xing-Long
Abstract : In this study, Sb0.7 Bi0.3 PS4 exhibits enhanced Na-storage performance through Bi 3+ substitution. This ion substitution provides a strategy for advanced thiophosphate anodes in sodium-ion batteries. Abstract : The SbPS4 material has become a research hotspot in sodium ion battery anode due to its high specific capacity. Herein, we propose an effective strategy of Bi 3+ substitution in SbPS4 to improve the electrochemical performance during long-term charge and discharge processes. Compared with the specific capacity of 574 mA h g −1 of SbPS4, the Sb0.7 Bi0.3 PS4 material delivers a higher value of 831 mA h g −1 at 0.1 A g −1, which is a 30.9% improvement. The improvement in the electrochemical performance was attributed to the introduction of Bi active element, which can reduce large volume changes and enhance the ion and electron conductivities of SbPS4 . In addition, we have proved that pseudo-capacitance control in kinetic behaviors is instrumental for fast Na + transport in Sb0.7 Bi0.3 PS4 (92.1% of the total capacity comes from the capacitive contribution at 1.0 mV s −1 ). Moreover, the full battery exhibited excellent rate performance (122.9 mA h g −1 at 0.1C and 102.7 mA h g −1 at 1C) when paired by a Sb0.7 Bi0.3 PS4 anode and a Na3 V2 (PO4 )2 O2 F cathode.